Risky Punishment and Reward in the Prisoner's Dilemma - Peter Duersch; Maros Servátka (University of Heidelberg, Department of Economics, 2007)
We conduct a prisoner's dilemma experiment with a punishment/reward stage, where punishments and rewards are risky. This is compared with a risk free treatment. We find that subjects do not change their behavior in the face of risky outcomes. Additionally, we measure risk attitude and the emotions of subjects. While we find a strong influence of emotions, individual risk aversion has no effect on the decision to punish or reward. This is good news for lab experiments who abstract from risky outcomes. From the perspective of social preferences, our results provide evidence for risk neutral inclusion of other player's payoffs in the decisionmaker's utility function.
Keywords: 330; Prisoner's dilemma; risk; punishment; reward; emotions; experiment; Gefangenendilemma; Entscheidung unter Risiko; Test; Emotion